Bioaugmented removal of 17β-estradiol, nitrate and Mn(II) by polypyrrole@corn cob immobilized bioreactor: Performance optimization, mechanism, and microbial community response. (15th April 2022) - Gao, Zhihong; Ali, Amjad; Su, Junfeng; Chang, Qiao; Bai, Yihan; Wang, Yue; Liu, Yu
Abstract: The coexistence of nitrate and endocrine substances (EDCs) in groundwater is of global concern. Herein, an efficient and stable polypyrrole@corn cob (PPy@Corn cob) bioreactor immobilized with Zoogloea sp. was designed for the simultaneous removal of 17β-estradiol (E2), nitrate and Mn(II). After 225 days of continuous operation, the optimal operating parameters and enhanced removal mechanism were explored, also the long-term toxicity and microbial communities response mechanisms under E2 stress were comprehensively evaluated. The results showed that the removal efficiencies of E2, nitrate, and Mn(II) were 84.21, 82.96, and 47.91%, respectively, at the optimal operating conditions with hydraulic retention time (HRT) of 8 h, pH of 6.5 and Mn(II) concentration of 20 mg L −1 . Further increased of initial E2 (2 and 3 mg L −1 ) resulted in the inhibiting effect of denitrification and manganese oxidation, but excellent E2 removal efficiencies maintained, which were associated with the formation and continuous accumulation of biomanganese oxides (BMO). Characterization analysis of biological precipitation demonstrated that adsorption and redox conversion on the BMO surface played key roles in the removal of E2. In addition, different levels of E2 exposure are decisive factors in community evolution, and bioaugmented bacterial communities with Zoogloea as the core group can dynamically adapt to E2 stress. This study offers the possibility to better utilize microbial metabolism and to advance opportunities that depend on microbial physiology and material characterization applications. Graphical abstract: Image 1 Highlights: An original microbial immobilized biomaterial polypyrrole@corn cob was developed. 17β-estradiol, nitrate, and Mn(II) were effectively removed by the bioreactor. Adsorption and redox conversion facilitate the 17β-estradiol removal. Zoogloea was the dominant contributor for the high performance of bioreactor. Microbial communities in bioreactor can dynamically adapt to 17β-estradiol stress.